2013
DOI: 10.1063/1.4803275
|View full text |Cite
|
Sign up to set email alerts
|

Cluster measurements at CLOUD using a high resolution ion mobility spectrometer-mass spectrometer combination

Abstract: Articles you may be interested inCombining high mass resolution and velocity imaging in a time-of-flight ion spectrometer using pulsed fields and an electrostatic lens Rev. Sci. Instrum. 78, 083104 (2007) Abstract. Mass spectrometry is powerful tool for environmental and atmospheric chemistry analysis. Modern mass spectrometers demonstrate low detection limits, high sensitivity, and high resolving power. However, such high performance is not always enough to identify ambient ion clusters due to the clusters br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…At the same time, modeling of particle formation has also advanced greatly in the past few years. For the first time, simulations involving no empirical fitting parameters give qualitatively correct predictions for the sulfuric acid concentration dependence of cluster concentrations (Olenius et al, 2013b) and particle formation rates (Almeida et al, 2013), although quantitative agreement with experimental findings is still far from perfect.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…At the same time, modeling of particle formation has also advanced greatly in the past few years. For the first time, simulations involving no empirical fitting parameters give qualitatively correct predictions for the sulfuric acid concentration dependence of cluster concentrations (Olenius et al, 2013b) and particle formation rates (Almeida et al, 2013), although quantitative agreement with experimental findings is still far from perfect.…”
Section: Introductionmentioning
confidence: 88%
“…The details of the process have, however, remained poorly understood until lately. Recent laboratory experiments (Berndt et al, 2010;Benson et al, 2011;Almeida et al, 2013) have confirmed that particle formation rates of the magnitude observed in the atmosphere can be produced with ambient sulfuric acid concentrations and low concentrations of base molecules, giving new support for sulfuric acid being at least one of the compounds driving atmospheric particle formation. Also, ions have been suggested to play a role in atmospheric cluster formation (Yu and Turco, 2000), as ions are produced constantly by cosmic rays and radon decay, and small ionic clusters are more stable than their neutral counterparts.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kupiainen-Määttä: A Monte Carlo approach for determining cluster evaporation rates istry. This approach has been shown to give qualitative agreement with experiments (Almeida et al, 2013;Olenius et al, 2013b), but several very drastic assumptions are involved. First-principles molecular dynamics simulations (Loukonen et al, 2014a, b) have shown that one harmonically oscillating cluster structure is far from a realistic description of the thermal motion of molecules in a small electrically neutral cluster, as molecules may rotate inside the cluster, continuously breaking intermolecular bonds and forming new ones.…”
Section: Introductionmentioning
confidence: 64%
“…Also, evaporation rates estimated from quantum chemical Gibbs free energies Almeida et al, 2013) are presented in Table 1 for comparison. The theoretical evaporation rates have an uncertainty of one or two orders of magnitude, as they depend exponentially on the stepwise cluster formation energies, which have an uncertainty of 1-2 kcal mol −1 .…”
Section: Evaporation Rates From the Analysismentioning
confidence: 99%